2014
DOI: 10.1186/1556-276x-9-153
|View full text |Cite
|
Sign up to set email alerts
|

Optimum deposition conditions of ultrasmooth silver nanolayers

Abstract: Reduction of surface plasmon-polariton losses due to their scattering on metal surface roughness still remains a challenge in the fabrication of plasmonic devices for nanooptics. To achieve smooth silver films, we study the dependence of surface roughness on the evaporation temperature in a physical vapor deposition process. At the deposition temperature range 90 to 500 K, the mismatch of thermal expansion coefficients of Ag, Ge wetting layer, and sapphire substrate does not deteriorate the metal surface. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 33 publications
1
31
1
Order By: Relevance
“…The surfactants are deposited onto the surface of a substrate as a wetting or seeding inducer with a thickness ranging from less than a monolayer to a few monolayers. Numerous studies reported a transition from the 3D growth mode of noble‐metal films to a 2D growth mode in the presence of metallic surfactants, such as Al, Au, Cu, Ge, Ca, Nb, Sb, Cr, Ni, Sn, and Ti, as summarized in Table . The basic working principle of metal surfactants has been ascribed to either a kinetic description related to the surface mobility of the metal atoms or a thermodynamic description related to the surface free energy .…”
Section: Technical Issues In Ultrathin Metal Film Growthmentioning
confidence: 99%
“…The surfactants are deposited onto the surface of a substrate as a wetting or seeding inducer with a thickness ranging from less than a monolayer to a few monolayers. Numerous studies reported a transition from the 3D growth mode of noble‐metal films to a 2D growth mode in the presence of metallic surfactants, such as Al, Au, Cu, Ge, Ca, Nb, Sb, Cr, Ni, Sn, and Ti, as summarized in Table . The basic working principle of metal surfactants has been ascribed to either a kinetic description related to the surface mobility of the metal atoms or a thermodynamic description related to the surface free energy .…”
Section: Technical Issues In Ultrathin Metal Film Growthmentioning
confidence: 99%
“…One of the pairs of materials which exhibit segregation is silver and germanium . This combination was rediscovered for plasmonic applications when 1–2 nm thin germanium (Ge) wetting films were proposed to overcome silver (Ag) tendency to form clusters rather than smooth layers . However, it has been recently shown that the penetration of Ge atoms along high‐diffusivity paths in silver not only changes the resistivity of silver thin films but also has a significant impact on their optical properties …”
mentioning
confidence: 99%
“…The position of the resonances can be also controlled by changing the size of the silver grains. Different sizes can be obtained by, e.g., varying the substrate temperature during the evaporation process, altering the amount of Ge atoms or modifying the thickness of the Ag film. The measured spectra of the imaginary part of the effective permittivity of the Ag/Ge composite obtained with the Ag films of different thicknesses 100, 20, and 10 nm show that similar to the plasmonic nanoparticles of decreasing diameter, thinner films and, thus, smaller grain diameters lead to the shift of the LSP mode toward shorter wavelengths (Figure e).…”
mentioning
confidence: 99%
“…The same is possible for nanostructured surfaces of the electrodes, however their fabrication is more complicated than simple wet synthesis. In this case, the exact control of the structuring of achieved layers requires that at first they are very smooth, which in turn requires exact control of a substrate temperature and deposition ratein the sputtering process [16][17][18]. Furthermore, evaporation of ultrasmooth metal nanolayers is possible by using wetting layers such as e. g. germanium.…”
Section: Simulations Of Absorption Coefficients Of Polyazomethine-(fumentioning
confidence: 99%